Investigating the effect of media messages on sustainable development agenda acceptance among public in the United Arab Emirates - Youssef, Enaam; Abdellatif, Soumaya; Badr, Amal Mohamed Nabil; Mohamed Nasef, Saeed Amin (Frontiers in Communication, 2026)
This research seeks to examine how media messages influence the public’s acceptance of sustainable development goals in the United Arab Emirates. Drawing on the Diffusion of Innovation theory, 532 structured surveys are used to collect data, which is further scrutinized using structural equation modeling. Results showed an overall effective role of media messages in shaping public opinion regarding sustainable development. Respondents agreed that media messages regularly provide information about sustainable development that is accurate and based on diverse topics, affecting their perceptions and views regarding sustainable development goals. Results showed a wider agreement that these media messages affect public behavior on both individual and collective levels to accept sustainable development. The effectiveness of these media messages is further shown as the audience considers these messages as well-organized, well-represented, having symbolic meaning, and having stronger relevance. These messages are compatible as they are comprehensive and understandable, providing reliable information that is relevant to the audience’s needs both on collective and individual levels. Finally, the credibility of these messages is also indicated by the respondents agreeing that the sources can be trusted as it is unbiased and aimed at overall national development. Thus, this study underlines the significant role of media messages in fostering sustainable development agendas in the UAE. It highlights how the media actively encourages and contributes to attaining sustainable development goals. As the UAE aims for a sustainable future, the positive influence of media has the potential to encourage informed public opinion and contribute to collective efforts for a more sustainable and resilient society.